Scutellarein ameliorates dextran sulfate sodium-induced ulcerative colitis by inhibiting colonic epithelial cell proinflammation and barrier disruption - Tang, Qinglian; Jia, Haidong; Qin, Xu; Lu, Zhaowen; Huang, Wenjie; Wang, Yujing; Cao, Zhengyu (Frontiers in Pharmacology, 2024)
Scutellarein (Scu) is a natural occurring flavonoid found in multiple traditional Chinese medicines such as Oroxylum indicum (L.) Kurz and Scutellaria baicalensis, with various pharmacological activities including anti-inflammation, anti-oxidation and myocardial protection. Here, we investigated the therapeutic efficacy of Scu on dextran sulfate sodium (DSS) induced ulcerative colitis (UC) and the underlying mechanism. Gavage of Scu significantly decreased the DAI score, improved colon shortening, ameliorated the pathological score in DSS-treated mice with better efficacy than the positive drug, 5-aminosalicylic acid. Scu also inhibited the expression levels of cytokines (Il-1β, Tnf-α, Il-1α, Il-6, and Cxcl1) as well as barrier proteins (E-cadherin, Occludin, and ZO-1) in colon tissues of DSS mice. In intestinal epithelial HT-29 cells, Scu attenuated the IL-1β-downregulated expression levels of E-cadherin, occludin, and ZO-1, while reduced IL-1β-upregulated IL-6 and IL-8 mRNA levels. Moreover, Scu inhibited the phosphorylation and nuclear translocation of NF-κB and suppression of NF-κB phosphorylation abolished IL-1β-disrupted epithelial barrier integrity and IL-1β-upregulated proinflammatory mediator expression in HT-29 cells. These data demonstrate that Scu is an efficacious therapeutic agent to treat UC. Inhibition of inflammatory responses and maintenance of epithelial barrier integrity through NF-κB signaling pathway underlines Scu therapeutic effect on UC.